Design and Test of a Tangential-Axial Flow Picking Device for Peanut Combine Harvesting - Hongguang Yang; Mingzhu Cao; Bing Wang; Zhichao Hu; Hongbo Xu; Shenying Wang; Zhaoyang Yu (Agriculture, 2022)
This study presents a tangential-axial flow picking device for peanut combine harvesting. The device was designed with reference to the tangential-axial flow threshing mechanism of the grain combine harvesters. The main purpose of this study was to solve the problem of the high rate of loss and damage in the picking operation of the peanut combine harvesters in China. Through the theoretical analysis and design calculation of the key components of the peanut picking device, the structural and working parameters were determined. The orthogonal test was carried out by taking the feeding amount of the peanut plant, the picking clearance, the speed of the tangential cylinder, and the speed of the axial cylinder as the test factors. Additionally, the non-picking loss rate, entrainment loss rate, and damage rate of the peanut pods were used as the test indexes. The test results were analyzed by range analysis and analysis of variance, and the test parameters were optimized by fuzzy comprehensive evaluation method. The optimal parameter combination for the tangential-axial flow picking device was determined as follows. The feeding amount of the peanut plant was 2 kg/s, the picking clearance was 35 mm, the speed of the tangential cylinder was 360 r/min, the speed of the axial cylinder was 425 r/min. At this time, the non-picking loss rate was 0.52%, the entrainment loss rate was 0.54%, and the damage rate was 0.75%. The test results fully met the standard requirements of the peanut picking operation. This research provides a technical basis for the application of the tangential-axial flow picking device in peanut combine harvesters.